A new bizarre species of Euconnus (Cladoconnus) in Upper Eocene Rovno amber (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł; Perkovsky, Evgeny E. (Zootaxa, 2021)
Despite being among the most species-rich extant animal genera, Euconnus Thomson is rare in fossil record. Merely six species found in relatively young, Eocene and Oligocene ambers have been placed in this genus, which currently includes over 2,600 extant nominal species distributed worldwide. We describe †Euconnus nathani sp. n., the first extinct, unambiguously placed member of the broadly distributed, extant Palaearctic subgenus Cladoconnus Reitter, based on a unique male specimen in Upper Eocene Rovno amber, Ukraine. The male of the new species has monstrously modified antennae, in general structure showing close similarities to those of extant congeners, but the modification of antennomere 8 is so profound and bizarre that this one antennal segment alone is sufficient to identify adults of E. nathani.